PENERAPAN MODEL PEMBELAJARAN CTL (CONTEXTUAL TEACHING AND LEARNING) UNTUK MENINGKATKAN MINAT DAN PARTISIPASI BELAJAR MAHASISWA - Novi Mayasari (Universitas PGRI Madiun, 2016)
This research is a Classroom Action Research (CAR) which is meant to understand whether or not the implementation of CTL Model can improve student’s interest and participation in learning of First year students of Calculus 1 class in their first semester of IKIP PGRI Bojonegoro in academic year of 2015/2016. The result shows that the application of CTL model can improve student’s interest and participation in learning of first year students in Calculus 1class in IKIP PGRI Bojonegoro in academic year of 2015/2016.